Петр Чайковский. Места счастливого детства - Минин Рудольф Андреевич (Удмуртия, 2018)
Экземпляры: ф.15 (20200825) / Инвентарный номер: 52578 / Цена: 200.00 / Авт.знак: М 61 / ГРНТИ: 18.41 / ББК: 85.313(2Рос.Удм)